O Arquivo Público do Estado do Pará como difusor sociocultural: as múltiplas percepções da sociedade sobre o arquivo (2011-2018) - MORAES, Zilmilene Costa de (2022)
Within the scope of archival functions diffusion is one of the functions that best serves the dissemination of information in archives. This is presented through methodologies aimed at educational, editorial and cultural diffusion, involving complementary topics such as mediation and access. Faced with the emerging technological advance of a post-World War II, a factor that contributed to the changes in the way society relates to cultural institutions such as: museum, theater, library and archive, which ends up encouraging professionals in the area to rethink in the renewal of traditional diffusion methodologies, with the purpose of relating and allying technologies and mediation in this process. The study of users and the perception they have of archival institutions, give us support for the use of sociocultural mediation, covering education and promotion, dissemination of archives services and activities, as well as the development of cultural projects. Therefore, the Public Archive of the State of Pará has as its object of study and as a general objective, it seeks to demonstrate the multiple perceptions that society has towards this, deriving, therefore, the specific objective that is intended to understand, reflect and analyze the best way to carry out sociocultural diffusion. It is understood that the diffusion in archives requires more in-depth studies on the subject, since, as classification and evaluation phases are more approached, due to the fact that many Brazilian archives are focused on the development of technical activities of organization and elimination of documents, postponing a of the functions that best fit the social function of the archivist.